(untitled) - Asher, Nicholas (Cambridge UK, 2003)
Logics of Conversation presents a dynamic semantic framework called Segmented Discourse Representation Theory, or SDRT, where this interaction between discourse coherence and discourse interpretation is explored in a logically precise manner. Combining ideas from dynamic semantics, commonsense reasoning and speech act theory, SDRT uses its analysis of rhetorical relations to capture intuitively compelling implicatures.
Keywords: Semantics,Ngữ nghĩa học,Discourse analysis,Phân tích luận